The Stardom Film Creating the Hollywood Fairy Tale. - McNally, Karen (Short cuts., 2020)
Since the movie industry's earliest days, Hollywood has mythologized itself through stories of stardom. In the first book to focus exclusively on these modern fairy tales, Karen McNally traces the history of this genre from silent cinema to contemporary film and television to show its significance to both Hollywood and broader American culture.